Exploring the impact of COVID-19 on private sector SMME incubation support in South Africa - De Waal, Anelia (Graduate School of Business (GSB), 2024)
The COVID-19 pandemic had globally disruptive repercussions, resulting in the resiliency of numerous support systems being tested, including the support ecosystem for small, micro, and medium-sized enterprises (SMMEs). Small business development initiatives, such as incubation and acceleration programmes, ostensibly provide a supportive environment for SMMEs to overcome economic pressures and market failures. They provide a critical role in the development of SMMEs and, by extension, healthy, inclusive economies. Given the catastrophic impact of the COVID-19 pandemic on the number of SMMEs closing down, particularly in South Africa, ensuring that future support mechanisms are geared towards adaptability and resiliency is imperative. In pursuit of this, efforts to understand how enterprise support organisations involved in incubation-style small business development programmes experienced the COVID-19 pandemic is a critical step in developing frameworks for future crisis responses. In aid of this goal, the research project focused on the experiences of 12 practitioners representing enterprise support organisations, using qualitative research methods to code and compare emerging experiences. The research found a correlation between the influence of power and agency on multi-level decision-making, and how this determines capacity to adapt and respond in inclusive and meaningful ways. It is the recommendation of this study that small business development organisations develop adaptive support practices that centre inclusivity and leverage micro-agency. Key mechanisms found in the study include the adoption of limited hierarchical operation practices, open dialogue that prioritises collaboration, and continuous learning and improvement initiatives. Future research needs to be conducted from the perspective of SMMEs within development programmes during COVID-19, to bolster the study findings, and aid in determining the degrees to which support initiatives were effective.